Evaluation of efficacy, pharmacokinetics and tolerability of peptidomimetic aspartic proteinase inhibitors as cream formulation in experimental vaginal candidiasis. (13th March 2014) - De Bernardis, Flavia; Arancia, Silvia; Tringali, Giuseppe; Greco, Maria Cristina; Ragazzoni, Enzo; Calugi, Chiara; Trabocchi, Andrea; Sandini, Silvia; Graziani, Sofia; Cauda, Roberto; Cassone, Antonio; Guarna, Antonio; et al.
Abstract Objectives It has been previously shown that the treatment with the two protease inhibitors APG12 and APG19 confers protection in a rat model of mucosal candidiasis; in this study, we examined whether these peptidomimetic inhibitors are also effective as a cream formulation in reducing Candida albicans vaginal infection. Methods These efficacy studies were performed in a rat model of estrogen‐dependent rat vaginitis by C. albicans on both azole‐susceptible and azole‐resistant C. albicans, and on both caspofungin‐susceptible and caspofungin‐resistant C. albicans strains. In vivo studies were also conducted in female albino rats and rabbits to obtain information about the safety, local tolerability and principal pharmacokinetics parameters of the two compounds. Key findings and conclusions Both hit compounds showed remarkable results within the 48‐h range as effective inhibitors of the infection, particularly causing rapid decay of vaginal C. albicans burden. Importantly, the two compounds showed marked acceleration of fungus clearance in the rats challenged with the fluconazole‐resistant as well as with the capsofungin‐resistant strain of C. albicans. Both compounds showed fast elimination rates when given by the intravenous route, and poor systemic absorption after intravaginal cream administration. Test drugs were also well tolerated in 7‐day local tolerability experiments in the rabbit.